Problematika Tata Kelola Aset Bersejarah: Studi Kasus di Provinsi Sumatera Barat - Indah Siti Aisyah Erwis; Deviani Deviani (Jurnal Eksplorasi Akuntansi, 2024)
This research aims to find out the governance of historical assets in West Sumatra Province, find out how historical assets should be valued for financial statements in pursuit of good governance. And find out what obstacles and challenges are faced in realizing the governance of historical assets. This type of research is qualitative research so this research uses a combined type of data from primary data and secondary data. Data collection by means of observation, interviews and documentation. Qualitative data analysis techniques occur interactively and take place continuously until completion, so that the data becomes valid by reducing data, presenting data and drawing conclusions. The results of this study are Based on the results of the presentation and discussion, it can be seen that the historic assets in West Sumatra are managed by the West Sumatra Cultural Heritage Preservation Center, the West Sumatra Culture Office and the local city / district education and culture office are as follows The governance of historic assets that have been implemented by the cultural heritage preservation agency and the West Sumatra provincial government is in accordance with the theory of Good Governance.